2023
DOI: 10.1111/irv.13101
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices towards seasonal influenza vaccination among pregnant women and healthcare workers: A cross‐sectional survey in Afghanistan

Abstract: Background Despite recommendation by the World Health Organization (WHO), influenza vaccination coverage among high‐risk groups remains suboptimal in Afghanistan. This study aims to document the knowledge, attitudes, and practices of seasonal influenza vaccine uptake among two priority groups, pregnant women (PWs) and healthcare workers (HCWs). Methods This cross‐sectional study enrolled PWs and HCWs in Kabul, Afghanistan, from September to December 2021. Data on vaccine intention and uptake, knowledge, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These coverage estimates are higher than previous surveys from Pakistan, which report around 8.8–20.1% of the healthcare workers to be vaccinated and are comparable with other WHO Eastern Mediterranean Region countries. 13 , 16-18 The HCWs in our study had a low level of awareness, as only 25% of them ever made a laboratory-confirmed diagnosis of influenza in their practice and 39% of the HCWs did not perceive themselves to be susceptible to severe disease. Previously, Ali et al reported that 60% of the HCWs believed asymptomatic hospital workers cannot transmit the virus and the vaccine contains a live virus which may cause influenza.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These coverage estimates are higher than previous surveys from Pakistan, which report around 8.8–20.1% of the healthcare workers to be vaccinated and are comparable with other WHO Eastern Mediterranean Region countries. 13 , 16-18 The HCWs in our study had a low level of awareness, as only 25% of them ever made a laboratory-confirmed diagnosis of influenza in their practice and 39% of the HCWs did not perceive themselves to be susceptible to severe disease. Previously, Ali et al reported that 60% of the HCWs believed asymptomatic hospital workers cannot transmit the virus and the vaccine contains a live virus which may cause influenza.…”
Section: Discussionmentioning
confidence: 68%
“… 12 The questionnaire is pre-validated and previously tested for reliability and item selection and is being currently used in KAP studies by PIVI in Low-and Middle-Income countries (LMICs). 13 The study tool was designed to inquire about the demographic information of the healthcare workers (HCWs) and pregnant women (PW), their vaccination status, the reasons for not receiving the influenza vaccination, and the general knowledge of influenza disease and vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also reported psychological barriers to vaccine acceptability (Adeyanju et al, 2021). Shahid et al (2023) and Arriola et al (2018) further showed that the pregnant population's shared concerns about the cost of the vaccine and limited awareness are universal barriers that exist in many cultures and socio-economic settings.…”
Section: Discussionmentioning
confidence: 99%